Class and the Dirty Work of War in Calderón - Greer, Margaret R. (Anuario Calderoniano, 2014)
One of the never-ending debates among critics of the drama of Pedro Calderón de la Barca revolves around the punishment of the rebel soldier in La vida es sueño who sparked the rebellion that overthrew Basilio and brought Segismundo to power. Some argue that it is patently unjust; others attribute it to a prudent reason of state that condemns treachery to the established order even to achieve a desired end, and blame the soldier’s self-serving claim that he deserves a reward. This article illuminates that debate from the perspective of several other Calderonian dramas of war and rebellion: El sitio de Breda, El Tuzaní de la Alpujarra, La aurora en Copacabana, El divino cazador and El segundo Scipión. Bringing into my treatment consideration of the changing status of military service in early modern Spain as the army became semi-professional, I argue that Calderón regularly assigns the dirty but necessary work of war to self-serving actions of lower-class characters whom he depicts unfavorably, thereby safeguarding an aristocratic ideology of the nobility of military service by upper-class officers. «Clase y “trabajo sucio” en la guerra calderoniana» Uno de los eternos debates entre los calderonistas es el del castigo del soldado rebelde que incendió la rebelión para derrocar a Basilio y coronar a Segismundo en La vida es sueño. Algunos arguyen que su encarcelación final es injusta; otros atribuyen el castigo a una prudente razón de estado que condena la traición al orden establecido y culpa al soldado por pedir una recompensa personal. Este ensayo ilumina algunos puntos de ese debate desde la perspectiva de otros dramas calderonianas de guerra y rebelión: El sitio de Breda, El Tuzaní de la Alpujarra, La aurora en Copacabana, El divino cazador y El segundo Scipión. Incluyo en mi análisis los cambios en el servicio militar en la España de la primera modernidad, cuando el ejército se hizo semi-profesional, arguyo que Calderón suele asignar el «trabajo sucio» de la guerra a las acciones egoístas de soldados villanos para así salvaguardar una ideología aristocrática de la nobleza del servicio militar por oficiales de la clase alta. PALABRAS CLAVE / KEYWORDS: Clase, guerra, «trabajo sucio», Calderón / Class, war, «dirty work», Calderón